Audiovestibular manifestations in patients with rheumatologic diseases: a review - Palacio, Valentina; Madrigal, Jorge; Garcia, Alejandro; Castillo-Bustamante, Melissa (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Rheumatologic disorders are chronic and systemic disorders with an estimated global prevalence of 3,200 per 100,000 inhabitants. Several clinical manifestations are known and may lead to physical disability and altered quality of life. The most common audio vestibular manifestations commonly reported are hearing loss, tinnitus, vertigo, and fullness, however, there are some more still unregistered. The aim of this review is to describe the most common audio vestibular features in three of the most common rheumatologic conditions such as rheumatoid arthritis (RA), systemic erythematous lupus and systemic sclerosis (SSc). A literature search was performed with articles published between 2000 to 2021. In this literature review an increased prevalence of hearing loss for RA of 40% and 70% for systemic erythematous lupus was observed. In SSc, due to its early onset and progression, there is no estimated prevalence, however, a notorious hearing impairment in early stages of the disease was described. Vertigo was also described in these disorders, affecting more than 60% of patients. Further studies are in need to describe the affection on early stages of all disorders as well as its progression.